Gnathostoma binucleatum (Spirurida: Gnathostomatidae) en peces dulceacuícolas de Tabasco, México - Kifune, Teiji; Lamothe-Argumedo, Rafael; García-Prieto, Luis; Oceguera-Figueroa, Alejandro; León-Règagnon, Virginia (Revista de Biología Tropical, 2004)
Human gnathostomiasis is a food-born parasitic disease of relative importance in many countries in Southeast Asia. It is caused by several species of nematodes of the genus Gnathostoma. In Mexico is an emerging public health problem since 1970, when first cases were reported. Until today, larval morphometric characters that have been proposed to differentiate between the three species of Gnathostoma present in this country, are not satisfactory. Recently, the presence of advanced third-stage larvae AdvL3 (infective form for humans) in freshwater fishes from Pantanos de Centla, Tabasco, was recorded but their specific identity was not clarified . Examination of four species of freshwater fishes from the same locality revealed that three of them: Petenia splendida (n=58), Cichlasoma managuense (n=35) and Gobiomorus dormitor (n=9) were infected by 15 AdvL3 of Gnathostoma binucleatum. Specific identity was obtained comparing the internal transcribed spacer 2 (ITS2) of the ribosomal DNA with sequences reported in Genbank. This is the first record of G. binucleatum in P. splendida and G. dormitor from Tabasco and the first specific determination of the parasite in the locality.